2017
DOI: 10.1080/17435390.2017.1415389
|View full text |Cite
|
Sign up to set email alerts
|

Research on the hepatotoxicity mechanism of citrate-modified silver nanoparticles based on metabolomics and proteomics

Abstract: Citrate-modified silver nanoparticles (AgNP-cit) have received extensive attention due to their excellent antimicrobial properties. However, these particles tend to migrate in vivo, thereby entering the blood circulatory system in granular form and accumulating in the liver, causing toxic reactions. However, the mechanism underlying AgNP-cit toxicity is not yet clear. Thus, we adopted a tandem mass tag (TMT)-labeled quantitative proteomics and metabolomics approach to identify proteins and small molecule metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Likewise, amino acids have been minimally extended, and in opposition, creatine and phosphocreatine remained unaffected. The cholesterol esters of polyunsaturated fatty acids and PPC have been decreased [139,140]. On the contrary, from the previous literature, AgNPs-and Ag+-treated metabolome signatures delivered plenty similar landscapes, although a few variances were noted.…”
Section: Topology Of Membrane Metabolismmentioning
confidence: 69%
“…Likewise, amino acids have been minimally extended, and in opposition, creatine and phosphocreatine remained unaffected. The cholesterol esters of polyunsaturated fatty acids and PPC have been decreased [139,140]. On the contrary, from the previous literature, AgNPs-and Ag+-treated metabolome signatures delivered plenty similar landscapes, although a few variances were noted.…”
Section: Topology Of Membrane Metabolismmentioning
confidence: 69%
“…were the mechanism for DON-induced hepatotoxicity. Recent literature suggested that CYP450s are involved in oxidative stress, apoptosis and in ammatory response against foreign particles [39,40].…”
Section: Donmentioning
confidence: 99%
“…A low‐dose, long‐term exposure of human bronchial epithelial cells to AgNPs may induce fibrosis and epithelial‐mesenchymal transition, a process associated with cancer progression . Citrate‐modified AgNPs resulted in abnormalities in purine metabolism in rats . The intestinal microbiota may also be affected, since AgNPs may induce microbial alterations similar to those related to inflammatory diseases in rat guts .…”
Section: Inorganic Antimicrobial Nanostructuresmentioning
confidence: 99%
“…[24] Citrate-modified AgNPs resulted in abnormalities in purine metabolism in rats. [25] The intestinal microbiota may also be affected, since AgNPs may induce microbial alterations similar to those related to inflammatory diseases in rat guts. [26] Actually, Tian et al [27] reported that lactobacilli were more susceptible than two common pathogens (Escherichia coli and Staphylococcus aureus) to AgNPs.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%